Zoonotic diseases risk perceptions and protective behaviors of consumers associated with consumption of meat and milk in and around Bishoftu, Ethiopia. Issue 8 (August 2022) - Tsegaye, Dagne; Gutema, Fanta D.; Terefe, Yitagele
Abstract: Consumption of raw or undercooked milk and meat is a major source of zoonoses. Information on the public risk perceptions and protective behaviors are essential for prevention and control of these diseases. However, such information is limited in Ethiopia. We assessed the risk perceptions and protective behaviors of the community toward zoonoses associated with consumption of raw meat and milk by employing the basic constructs of food safety health belief model. We collected data from 210 respondents (105 from each urban and peri-urban) using a face-to-face questionnaire interview. Majority of the respondents (96.2%) had knowledge about zoonoses. Despite their knowledge, 91% and 94.3% had raw meat and raw milk consumption habits, respectively. The odds of raw meat consumption was significantly higher in males (AOR = 3.90; CI = 1.28–11.86) and raw milk consumption was higher in females (AOR = 3.82; CI = 0.78–18.65). About 65% of respondents, obtained meat from backyard slaughtering. Self-owned and smallholder dairy farms are the major sources of milk for peri-urban and urban dwellers, respectively. While 46.7% of the respondents reported that community members are the primary sources of information, only 2.4% reported animal health professionals as their primary source of information. More than half of the respondents either moderately or strongly agreed that consumption of raw meat and raw milk can expose them to zoonoses. Urban dwellers had perceived more seriousness of consuming raw animal products. Peri-urban residents had significantly lower intention than urban ones to implement protective behaviors such as stopping consuming raw meat (P = 0.017) and milk (P = 0.043). We noted that lack of access to refrigerator and pasteurized milk were the perceived barriers for protection against zoonoses among the peri-urban dwellers. There was significant difference in perceived benefits of avoiding consumption of raw meat (P = 0.005) and milk (P = 0.001) between urban and peri-urban residents. Our study showed that irrespective of knowledge about zoonoses, consumptions of raw meat and raw milk remained common practices among the respondents. Public health education on the risk of consumption of raw milk and meat and the significance of protective behaviors using a one-health approach is critically needed to ensure meat and milk safety. Abstract : Risk perceptions; Protective behaviors; Food safety belief model; Raw meat; Raw milk; Zoonoses; Bishoftu